Analisis Kebijakan Restorative Justice dalam Penanganan Kasus Penganiayaan Anak di Polrestabes Palembang - Nilawati; Raqin, Muhammad Dhiwa Azka; Utama, Cholidah; Lubis, Ramiah (Al-Ijtima`i: International Journal of Government and Social Science, 2026)
The development of modern criminal law is moving towards a restorative justice approach, which emphasizes the restoration of social relationships between perpetrators, victims, and the community. This study examines the application of restorative justice in cases of child abuse at the Palembang City Police Headquarters and its compliance with the principles of Islamic Criminal Law. The method used is empirical juridical with a qualitative approach, through interviews and field studies. The research results show that the case was resolved through mediation between the perpetrator and the victim's family, with consideration of the child's best interests. Restorative justice in child abuse cases at the Palembang City Police Headquarters, in accordance with Police Regulation No. 8 of 2021, resulted in a peace agreement, withdrawal of the report, and issuance of a letter of termination of investigation, thus resolving the case quickly, simply, and restoring the relationship between the parties. From an Islamic criminal law perspective, resolving criminal abuse through restorative justice aligns with the concept of al-ṣulḥ (peace) recommended in sharia, as long as it does not conflict with the principles of justice. In conclusion, the application of restorative justice can be a humane alternative in resolving child cases, but must be carried out selectively and carefully to avoid reducing legal protection for child victims.